Menggagas Pemasaran Kreatif: Peran Co-creation antara Akademisi, Pemerintah, dan UMKM - Sari, Filma Alia; Mujiono, Mujiono; Indrawati, Henny; Makhdalena, Makhdalena; Hakim, Muhd. Fikri; Putri, Sella Anggelia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Rural areas play an important role in regional economic development through the utilization of abundant natural resources. However, limited labor and capital often hinder the progress of the rural economy. Advanced MSMEs can be a solution to overcome this gap. This article discussed the challenges faced by rural MSMEs, such as limited facilities, access to resources, and lack of human capital. One proposed solution is to build networks between academics, businesses, and government to exploit new business strategies in rural areas. Partnerships in community service activities with MSME Silaturohim in Sidomukti Village demonstrated the importance of effective product packaging and marketing strategies to achieve sustainable business growth. A co-creation approach was used to identify and address problems faced by partners.